Wheat straw improved by half-rate application of anhydrous ammonia - Waggoner, Justin W.; Reid, R.; Oleen, Brandon E.; Hollenbeck, William R.; Holthaus, Jody G.; Sexten, A.; Petersilie, J.; Weaber, Robert L.; Johnson, S.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Many tons of crop residues and other low-quality forages are produced in Kansas each year. Use of these forages often is limited by their low nutrient content and poor digestibility. The process of applying anhydrous ammonia to low-quality forages enhances their feeding value by increasing crude protein content and dry matter digestibility. In the summer of 2012, the persistence of drought conditions throughout Kansas reduced forage supplies and resulted in a dramatic increase in forage prices. In an effort to aid livestock producers, the K-State Beef Extension Specialist Team, in conjunction with the Livestock Production Program Focus Team, conducted wheat straw ammoniation demonstrations at 6 locations across Kansas. The objectives of these demonstrations were to: (1) demonstrate the process of using anhydrous ammonia to treat low-quality roughages, and (2) determine if the recommended rate of 3% anhydrous ammonia application (dry weight) could be decreased as a cost-saving measure. The effects of two anhydrous ammonia application rates (1.5 and 3.0% dry matter weight of stack, equivalent to 30 or 60 lb anhydrous ammonia/ton of dry forage) on subsequent forage quality and digestibility were evaluated.
Keywords: Beef; Anhydrous ammonia; Forage quality; Digestibility; Crop residues